Effect of Physicochemical Factors on Cyanobacteria Biodiversity in Some Agricultural Soil of Al-Diwaniyah City during Spring Period - Haider A. Alghanmi (Journal of Global Pharma Technology, 2018)
The present study investigated the effect of some physicochemical factors on the biodiversity of Cyanobacteria In the agricultural soils of some areas in the city of Diwaniyah, where six areas are selected: Ghammas, Al-Shamiya, Al-Saniya, Afak, Al-Daghara, Al-sadeer with five farms per region during spring, Physical and chemical factors of the soil range between 21-23.5 °C and pH between 7.72-7.33, electrical conductivity between 233.8-3072 μs/cm, salinity between 0.268-1.730%, Nitrate between 7.46-20.0400 ppm, and phosphate between 1.340-5.260 ppm while the soil texture, the percentage of sand ranges between 12.08-15.68%, the Silt between 50.112-53.216%, and the clay between 34.208 -35.5%, the organic matter is between 3.350-6.202%, potassium 23-57ppm, calcium between 125.2-1320 ppm, magnesium between 51.46-557 ppm, and sodium between 1.3040-12.3580 ppm. Cyanobacteria species identified in this study are about 26 species. The dominant species of cyanobacteria represented by Oscillatoria sp. with percentage 50% followed by Phormidium sp.19.230%, then Chroococcus sp. and Spirulina sp. 7.692%, Finally, Gleocapsa sp., Microcoleus, sp. and Shizothrixsp. Reach to 3.864%. Some species of Cyanobacteria record in all soil areas like Oscillatoria acuta, O. Laetevirens, O. tenuis, Phormidium anomala, and P. pachydermiticum. The lowest number of Cyanobacteria is 2 in Afak and in Al-Sanyia and the highest number is 8 in Gammas. The Shannon Diversity index values of ranged between 2.350-2.685. While Simpson index Diversity values range between 0.935-0.960 in Afak and Ghamm as, respectively. The results of the statistical analysis showed significant differences and a positive, negative correlation between physicochemical factors and to the cyanobacteria numbers of some agricultural areas at p<0.05.Keywords: Cyanobacteria, Biodiversity, Soil, Physicochemical factors, Spring.